2020
DOI: 10.5334/tohm.59
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Home-use Study on Non-invasive Neuromodulation Therapy for Essential Tremor

Abstract: Highlights This prospective study is one of the largest clinical trials in essential tremor to date. Study findings suggest that individualized non-invasive neuromodulation therapy used repeatedly at home over three months results in safe and effective hand tremor reduction and improves quality of life for many essential tremor patients. Background: Two previous randomized, controlled, single-session trials demonstrated efficacy of non-invasive neuromodulation therapy targeting the median and radial nerves for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
92
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 41 publications
(135 citation statements)
references
References 48 publications
(112 reference statements)
3
92
0
2
Order By: Relevance
“…Similarly, the magnitude of acute (i.e., immediately poststimulation) tremor improvement reported in this study is consistent with the acute tremor improvements observed in previous TAPS studies. This study found an average FTM-CRS improvement of 0.6 points immediately after stimulation (Figure 2), which was comparable to improvements reported in other studies using similar clinical rating scales [0.3-0.8 point improvement in various upper limb tasks in the Tremor Research Group Essential Tremor Rating Assessment Scale (Elble, 2016), and 0.3-1 point improvement in the Bain & Findley Activities of Daily Living scale (Bain et al, 1993;Pahwa et al, 2019;Isaacson et al, 2020)]. The median 3.2-fold improvement (70% reduction) in postural hold tremor power immediately after the end of stimulation ( Figure 3A) in this study is comparable to the range of postural hold tremor power improvements reported in a 3 month at-home clinical trial (Isaacson et al, 2020).…”
Section: Discussionsupporting
confidence: 87%
See 4 more Smart Citations
“…Similarly, the magnitude of acute (i.e., immediately poststimulation) tremor improvement reported in this study is consistent with the acute tremor improvements observed in previous TAPS studies. This study found an average FTM-CRS improvement of 0.6 points immediately after stimulation (Figure 2), which was comparable to improvements reported in other studies using similar clinical rating scales [0.3-0.8 point improvement in various upper limb tasks in the Tremor Research Group Essential Tremor Rating Assessment Scale (Elble, 2016), and 0.3-1 point improvement in the Bain & Findley Activities of Daily Living scale (Bain et al, 1993;Pahwa et al, 2019;Isaacson et al, 2020)]. The median 3.2-fold improvement (70% reduction) in postural hold tremor power immediately after the end of stimulation ( Figure 3A) in this study is comparable to the range of postural hold tremor power improvements reported in a 3 month at-home clinical trial (Isaacson et al, 2020).…”
Section: Discussionsupporting
confidence: 87%
“…reduce or discontinue use of medications due to the side effects present at the doses required to sufficiently treat tremor (Koller and Vetere-Overfield, 1989;O'Suilleabhain and Dewey, 2002;Zesiewicz et al, 2005;Pal, 2011;Hedera et al, 2013). While TAPS has been shown here and in other studies to have a much lower adverse event rate than medications (Lin et al, 2018;Pahwa et al, 2019;Isaacson et al, 2020), this single-session study alone is insufficient to conclude whether 60 min of benefit after 40 min of stimulation is sufficient for some patients to adopt TAPS therapy into their tremor treatment routine. Future work to examine patient satisfaction with receiving 60 min of benefit after each therapy session, the time course of repeated TAPS throughout the day (i.e., mimicking medication usage), and how TAPS therapy interacts with medication usage would provide valuable guidance for physicians prescribing only TAPS, only medications, or TAPS and medication combined.…”
Section: Discussionmentioning
confidence: 61%
See 3 more Smart Citations